Teachers’ Attitude, Knowledge, and Implementation toward STEM based on Gender - A Halim; Supriatno Supriatno; Yusrizal Yusrizal; Mursal Mursal; Eviza Nurfadilla (Jurnal Penelitian Pendidikan IPA, 2022)
The STEM (Science, Technology, Engineering, and Mathematics) approach is one of the learning approaches that is able to answer the challenges of education in the era of globalization, which demands that human resources must have quality in order to compete globally. To achieve this, STEM-based learning can help, and to achieve successful learning with this STEM approach, the teacher is an important factor, because teachers as teachers and educators influence student learning outcomes and skills. The success factor of teachers in implementing STEM is influenced by backgrounds such as gender, therefore this study aims to see how the level of attitudes, knowledge, and practices of teachers in implementing the STEM approach. This research is a quantitative descriptive study using a survey method. This research was conducted in Aceh Province, Indonesia. The population of this study were science teachers (teachers who teach science, biology, chemistry, and physics). The total sample in this study was 267 samples, the number of samples of male teachers was 87 and the number of samples of female teachers was 180. The research data were processed using percentages. The results showed that male teachers and female teachers had the same level of attitude, knowledge, and practice, namely at a high level towards the STEM approach in learning.